Uma avaliaç\~ao final da focalizaç\~ao e da efetividade contra a pobreza do Programa Bolsa Família, em perspectiva comparada - Pedro H. G. Ferreira de Souza; Raphael Bruce (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– In this paper we evaluate how well-targeted and effective in reducing poverty the Bolsa Família Program (PBF) was in Brazil between 2004 and 2019. In order to do this, we use data from the National Household Sample Survey (PNAD) from 2004 to 2015, from the Continuous National Household Sample Survey (PNAD Continuous) from 2012 to 2019, and from the Atlas of Social Protection Indicators of Resilience and Equity (Aspire). We calculate several different targeting and poverty indicators over the entire period to obtain an overview of how successful the program was in both dimensions. Additionally, we provide an international comparison between PBF and conditional cash transfer programs in other countries. Our results indicate that PBF was well targeted, with low levels of inclusion errors (people who should not have received the benefit, but did) and moderate levels for exclusion errors (people who should have received the benefit, but did not). Moreover, from an international perspective, PBF was well targeted, ranking among the best programs in our sample, regardless of the poverty line or targeting metric used. With respect to the effect on poverty reduction, the results suggest an important role for PBF, especially when lower poverty lines are used. However, for these lines, the effect of PBF on poverty declined over time. In particular, there was no increase in the role of PBF on poverty reduction between 2012 and 2019. We conclude that any program that replaces PBF should prioritize the reduction of exclusion errors and the maintenance of the real value of the benefit.
10419/284869
Keywords: D31; H53; I32; O54; 330; Programa Bolsa Família; conditional cash transfer; targeting; poverty; Brazil